Satan the heretic: the birth of demonology in the medieval west - Boureau, Alain (The University of Chicago Press, 2014)
Satan the Heretic: the judicial institution of demonology under John XXII -- Satanic sacraments? Enrico del Carretto's discovery -- The pact: an overview -- The liberation of demons: the birth of scholastic demonology -- The new possessed: saints and demons in canonization trials at the beginning of the fourteenth century -- The openness of the subject: a scholastic anthropology of possession -- Supernatural invasions: mystical models of possession